Phagocytosis and Efferocytosis by Resident Macrophages in the Mouse Pancreas - Parv, Kristel; Westerlund, Nestori; Merchant, Kevin; Komijani, Milad; Lindsay, Robin S.; Christoffersson, Gustaf (Frontiers in Endocrinology, 2021)
The tissue microenvironment in the mouse pancreas has been shown to promote very different polarizations of resident macrophages with islet-resident macrophages displaying an inflammatory “M1” profile and macrophages in the exocrine tissue mostly displaying an alternatively activated “M2” profile. The impact of this polarization on tissue homeostasis and diabetes development is unclear. In this study, the ability of pancreas-resident macrophages to phagocyte bacterial and endogenous debris was investigated. Mouse endocrine and exocrine tissues were separated and tissue-resident macrophages were isolated by magnetic immunolabeling. Isolated macrophages were subjected to flow cytometry for polarization markers and qPCR for phagocytosis-related genes. Functional in vitro investigations included phagocytosis and efferocytosis assays using pH-sensitive fluorescent bacterial particles and dead fluorescent neutrophils, respectively. Intravital confocal imaging of in situ phagocytosis and efferocytosis in the pancreas was used to confirm findings in vivo. Gene expression analysis revealed no significant overall difference in expression of most phagocytosis-related genes in islet-resident vs. exocrine-resident macrophages included in the analysis. The islet-resident macrophages were not found to have any impairment in neither phagocytosis or efferocytosis compared to exocrine macrophages both in vitro and in vivo. In this study, pancreas-resident macrophages were shown to differ in their ability to phagocyte bacterial and endogenous debris depending on their microenvironment. This difference in abilities may be one of the factors polarizing islet-resident macrophages to an inflammatory state since phagocytosis has been found to imprint macrophage heterogeneity. It remains unclear if this difference has any implications in the development of islet dysfunction or autoimmunity.